If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 4 + -1(-14) Multiply -1 * -14 3x = 4 + 14 Combine like terms: 4 + 14 = 18 3x = 18 Solving 3x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 6 Simplifying x = 6
| -12+6x-4x=18 | | x^2+y^2+2x+4y-20=0 | | 105x+15x-225=25 | | -4(6m+1)=-17m-18 | | 10x-5(2x+4)=20 | | 7(8v+1)=231 | | 4a-3b=10 | | 10x-x-134=118 | | 1.5x+3x-4=10 | | 15p+7p= | | 2x^2-5x-133=0 | | S=D+pm | | 3*3/10+4=-3 | | -2W+5-3W-4=-9 | | 3*-7/4+4=-3 | | 2.4(2x-2)+2.2x= | | .06x+.5=.123 | | X+45=600 | | (11b-6)-5(2b+4)=-6 | | 10(x+5)=12(x-4) | | 17p+14+19=3 | | x=2*tanh(x) | | 14m=400.0 | | 10x+12=32 | | x=tanh(x) | | x-4.2=6 | | 12.67(a-3)=.5 | | 1.4y=7 | | -6(4x-3)+5(5x-4)-8=7-8 | | 2(y-2)-4=10 | | 2x^2-5x+245=0 | | -3n+9=-4n+5 |